OBSERVACIONES A LA TRADUCCIÓN LATINA DE G. LONGUEIL DE AETIA PHYSICA DE PLUTARCO - Morales Ortiz, Alicia (Myrtia, 1999)
In 1542 the dutch scholar Gilbert Longueil published a Latin translation of several treaties of Plutarco, which included a version of the work Aetia Physica. According to the own interpreter declaration -he says that he used the editio princeps of Aldus Manutius and also an exemplar mediolanense , which had been lost now- some interesting questions relating to textual criticism are analyzed in this paper.